Art and the Art of Theology - Shideler, Mary McDermott (Theology today, 1971)
“The most concrete manifestations of a theology, apart from words, occur in worship and ethics. How deeply any particular theologian should engage in such concrete affairs must, of course, be left to his individual decision. The artist can teach him, however, that the effort toward con-creteness—incarnation—will infuse his work with a vitality that cannot be obtained in any other way, and will test its validity more severely than any other form of examination.”